Evaluation methods for construction projects - Park, Moonseo; Chu, Yongsik; Lee, Hyun-Soo; Kim, Wooyoung (Journal of Civil Engineering and Management, 2009)
Financial evaluation methods such as Net Present Value (NPV) and Internal Rate of Return (IRR) are not fully adequate for accounting three practical aspects of construction projects: reinvestment rate, actual amount of required investment, and firm available funds. In a certain type of projects, this inadequacy often results in the inapplicability of NPV, multiple or no IRR problem, systematic bias of IRR, and inconsistent decision signal and ranking between NPV and IRR. Many modified methods have been developed, but hardly succeeded in reflecting construction market reality in an integrated manner. To address this issue, Project Present Value, Project Rate of Return, and Firm Rate of Return are proposed together with an investment decision framework. The proposed methods are designed to be free from all those problems, while incorporating market reality in them. As a result, construction practitioners would have more reliable and economically meaningful decision tools, which lead to the success of their projects. Santrauka Finansiniai įvertinimo metodai, kaip dabartinės vertės (DV) arba vidinės grąžos (VG), neadekvačiai vertina tris praktinius statybos projektų aspektus: reinvestavimo greitį, tikrąjį investicijų ir kapitalo poreikį. Dėl to neadekvatumo tam tikrai projektų rūšiai minėtųjų metodų iš viso neįmanoma pritaikyti. Sukurta daug modifikuotų metodų, tačiau jie sunkiai atspindi statybos rinkos tikrovę integruota forma. Tam pasiūlyta investicinių sprendimų sistema, į kurią integruoti trys metodai: dabartinės projekto vertės, projekto vidinės grąžos ir įmonės apyvartumo. Pasiūlytieji metodai gali įvertinti rinkos realybę. Dabar statybos gamybininkai turės patikimesnes ekonomiškai reikšmingas priemones sprendimams priimti ir galės sėkmingiau įgyvendinti savo projektus. First Published Online: 14 Oct 2010 Reikšminiai žodžiai: finansų valdymas, investicijos, sprendimų priėmimas.